PENGGUNAAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN DI MADRASAH IBTIDAIYAH - Suhendra, Ade (IAIN Padangsidimpuan, 2019)
This writing describe about using learning media based interactive multimedia on Primary Education by using Macromedia Flash. Using Macromedia Flash will be developedÂ the implementation ofÂ the quality learning. Based on this research, we find that after using Macromedia Flash, the students enjoyed the the learning and improve their motivation to study hard. Therefore, learning quality is improved by using Macromedia Flash.